Chemical characterization of wheat kernels naturally contaminated by deoxynivalenol-DON when cultivated under nitrogen management strategies - Souza, Thiago; Prando, André; Takabayashi-Yamashita, Cassia; Zucareli, Claudemir; Hirooka, Elisa (Revista Ciência Agronômica, 2019)
Chemical composition and contamination of wheat kernels (Triticum aestivum L.) directly affect the quality of the flour obtained from them, determining its acceptability and use by industry. Field trials were conducted to evaluate the effect of agricultural practices on wheat kernel quality (chemical composition and contamination). Cultivation was carried out following maize or soybean (crop succession), with application of nitrogen doses in topdressing (0, 30, 60, 90, and 120 kg ha-1), using seeds inoculated or not inoculated with Azospirillum brasilense. Data were subjected to analysis of variance (ANOVA), comparison of means by Tukey’s test (<0.05), and regression to nitrogen doses. Crop succession resulted in changes in kernel chemical composition (p<0.05), with exception for lipid content (p>0.05). Lower protein (-21.6%; p<0.05) and higher total carbohydrate content (+4.5%; p<0.05) were observed when wheat was cultivated after maize, in comparison with soybean succession, and no application of nitrogen in topdressing (0 kg ha-1). When cultivated after maize, protein content in the kernels was the factor with the greatest variation in response to increasing doses of nitrogen (11.1 to 16.5%, an increment up to 48.2% in the total content), due to a positive correlation with the independent variable (r>0.80; p <0.05). In terms of contamination by DON, 83.1% (133/160) of the samples presented contamination below the current maximum tolerated limit stablished by the Brazilian legislation for whole wheat flour (<1250 ug kg-1). Management of nitrogen availability can be recommended as an additional procedure to obtain raw materials with the desired chemical profile.